(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Buffalo milkers are more prone to de Quervain’s tenosynovitis due to their working process and repeated use of thumb, wrist and fingers. If there is any pain or problem in hand or wrist can have impact on milking ability which can lead to change in their economic status and quality of life. There are only few studies done on the population of buffalo milkers and problems regarding their occupation. Thus this study is designed to find prevalence of de quervain’s tenosynovitis in buffalo milkers. Aim: The aim of this study was to find out prevalence of de Quervain’s tenosynovitis in buffalo milkers and aware them about this condition to avoid further damage. Material and Method: Study was conducted with 92 subjects in and around Karad. Subjects were selected as per inclusion and exclusion criteria and consent was taken. Both males(43) and females(49) subjects were included for study. Then they were assessed with help of Finkelstein test and Visual analogue scale the data was collected and analysed accordingly. Stastical Analysis: The simple random sampling is used to select the subjects for study and it is conducted in and around Karad Taluka. The sample size was calculated by de quervain’s tenosynovitis taken at 64%. Hence for calculation of sample size p=64% and q=100-p=36% sample size n=4pq/L2 therefore n=92. Statistical analysis of the recorded data was done by using the software instat. MS Excel was used for drawing various graphs with given frequencies and the various percentages that were calculated with the software. Result: After analyzing the data, it was found that there is a prevalence of de Quervain’s tenosynovitis. In all participants 43% people have de Quervain’s tenosynovitis. It is found that prevalence of de Quervain’s tenosynovitis is more in females than males and pain distribution is more in age group of 41 to 45years. Conclusion: The prevalence of de Quervain’s tenosynovitis is more in females and precautions should be taken by buffalo milkers by modifying their work strategies to avoid further damage.